Cyanotic complex congenital heart disease presenting with brain abscess at the age of 19: A case report and review of literature - Sabah, Khandker Md Nurus; Chowdhury, Abdul Wadud; Islam, Mohammad Shahidul; Ahmed, Mohsin; Amin, Gaffar; Islam, Kazi Nazrul; Kawser, Shamima; Khan, HI Lutfur Rahman; Saleh, Mohammed Abaye Deen; Khan, Zayed Mahbub (Bangladesh Heart Journal, 2016)
Introduction: Brain abscess is a complication of congenital cyanotic heart disease with or without shunt anomaly. It is more common in children. Here, we delineated a case of 19-year-old young Bangladeshi - Bengali male who presenting with brain abscess, an unusual presentation of cyanotic complex congenital heart disease. This case report focuses not only on the unusual presentation of congenital heart disease but also emphasizes the importance of early recognition of neurological complication for referal management. Bangladesh Heart Journal 2016; 31(1) : 41-45